Towards a more Successful European Communication: Research Findings and Media Policy Recommendations - Balčytienė, Auksė; Juraitė, Kristina; Reingardė, Jolanta (Sociologija. Mintis ir veiksmas, 2015)
In the context of media developments world-wide including convergence of media system, journalism homogenization, diversification of political communication, it is important to understand how these processes will affect (trans)formation of the European public sphere. There has been no European news agenda across media in Europe so far, except for rare cases when European Union becomes an issue of top importance across Europe. Most often these are sensational events, crises or official meetings of the EU representatives. On the other hand, journalists are confronted with their audience, which is poorly informed and has inadequate knowledge about the EU. The aim of the article is to reassess the major challenges of European social imaginary by addressing key measures to be taken to communicate Europe effectively.